Effect of compressive stress in concrete on ultrasonic pulse velocity with different aspect ratios - Bong, Mei Lun. (Universiti Malaysia Sarawak, UNIMAS, 2010)
This study was conducted to explore the effect of compressive stress in concrete on the measured ultrasonic pulse velocity (UPV). Ultrasonic pulse velocities were measured by equipment called PUNDIT and test frame was used to test on the prisms concrete at the stress condition. The UPV values were measured at every load steps at 5% increment of the average compressive strength. This study was carried out by the concrete strength ranging from 25 to 30 N/mm2. The prisms with size of 100mm x 100mm x 200mm, 100mm x 100mm x 300mm and 100mm x 100mm x 400mm were used and tests were carried out at the age of 28 days. The tests results of these three prism sizes showed that almost similar characteristics. When the concrete prisms subjected with stress/ strength ratio from ranging 0.00 to 0.05, the UPV value increases slowly by 0.1% to 9%. After this state which is at 0.40 of stress/strength ratio, the UPV values increased rapidly. Under a higher compressive stress of 0.40 stress/ strength or higher, the measured of UPV values decreased rapidly but it greater than the original UPV value around 4% to 19%. The results obtained indicated that the compressive stress on concrete has significant effect on the measured of UPV values, particularly when the state of stress in the concrete is 40% or more of the compressive strength.